2014
DOI: 10.1088/0957-4484/25/4/045704
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the growth process of ultrathin silica shells on the surface of gold nanorods by the localized surface plasmon resonance

Abstract: Ultrathin silica coating (UTSC) has emerged as an effective way to improve the compatibility and stability of nanoparticles without attenuating their intrinsic optical properties. Exploration strategies to probe the growth process of ultrathin silica shells on the surface of nanoparticles would represent a valuable innovation that would benefit the development of ultrathin silica coated nanoparticles and their relevant applications. In this work, we report a unique, very effective and straightforward strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…Later on, Li et al reported on the formation of ultra-thin silica shell (UTSC) on MPTMS-capped AuNRs. The thickness of the silica shell was finely tuned in the 0.8–2.1 nm range by changing the amount of Na 2 SiO 3 [ 69 ]. These authors also investigated the rate of silica-shell growth using LSPR.…”
Section: Synthesis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, Li et al reported on the formation of ultra-thin silica shell (UTSC) on MPTMS-capped AuNRs. The thickness of the silica shell was finely tuned in the 0.8–2.1 nm range by changing the amount of Na 2 SiO 3 [ 69 ]. These authors also investigated the rate of silica-shell growth using LSPR.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“… ( A ) CTAB replacement by (3-mercaptopropyl)trimethoxysilane (MPTMS) for the growth of thin layers of silica. ( B ) and ( C ) TEM images obtained for different aspect ratio (AR) from ref [ 67 ] ( B ) and ref [ 69 ] ( C ). ( D ) Kinetics of silica shell thickness for decreasing concentrations of Na 2 SiO 3 from ref [ 69 ].…”
Section: Figurementioning
confidence: 99%
“…Moreover, Huang and co-workers considered that a 2–3 nm silica shell coated on Au NRs induces a highest sensitivity for plasmonic organic photovoltaic devices 30 . The recent theoretical calculation reveals that ultrathin silica coating (within 3.5 nm) would be ideal for improving the sensitivity 31 . Therefore, the aim of our present work is to explore the cut-off thickness in a small size, and further amplify the sensitivity of Au NRs maximally for practical application for detection of E. coli O157:H7.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports that under some circumstance, a protective layer can enhance the gure of merit when coated with Au and SiO 2 . 65,76,77 Thus, we conclude that the 1-BT treatment not only succeeded in stabilizing the sensor but also lead to improvements in the gure of merit, 208.9 and 170.43 nm per RIU for the 17 and 22 nm thick AgLSPR sensors respectively. Fig.…”
Section: Him Observation Of Unprotected and Protected Mfon Lspr Sensorsmentioning
confidence: 70%